Anti-aging activities of an ethanolic extract of Lycium ruthenicum in Caenorhabditis elegans based on metabonomic analysis - Cui, Boya; Liu, Lanying; Qiao, Xinmeng; Shi, Tao; Yin, Min; Xu, Shu; Feng, Xu; Shan, Yu (Frontiers in Pharmacology, 2025)
The fruits of Lycium ruthenicum Murr. (Solanaceae) are employed in ethnomedicine and used as a functional food. Their antioxidant, anti-aging, and hypolipidemic activities have been investigated in modern research. This study indicated that the ethanolic extract of the fruits of L. ruthenicum Murr. (LRM) improved oxidative and heat stress tolerance, reduced the accumulation of lipofuscin, and retarded the aging process in Caenorhabditis elegans (Rhabditidae). Furthermore, the pharyngeal pumping rate and body length decreased under LRM treatment. Moreover, metabolomic analysis and the DPClusO algorithm revealed that LRM regulated a series of lifespan-related pathways centered on glycine, serine, and threonine metabolism. These results suggest that LRM prolongs the lifespan of Caenorhabditis elegans via dietary restriction. Moreover, feruloyl putrescine, a kind of polyamine, was found in differential metabolites, which may be the metabolite of caffeoyl-spermidine in LRM. These findings from this exploratory study offer a new insight into the roles of L. ruthenicum in anti-aging activity as a functional food.